2008
DOI: 10.1089/pho.2007.2162
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Spectra of Blood Components for Breast Cancer Diagnosis

Abstract: Our statistical evaluation indicates that porphyrin in blood can be used as a reliable tumor marker. Fluorescence emission spectroscopy of blood components and statistical evaluations should be further investigated for a variety of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…It indicates that porphyrins accumulate more in tumor parts. The knowledge about the mechanisms of precursor 5-ALA lead to PpIX accumulation was demonstrated in many tumor diseases [48][49][50]. Our results showed that for the majority of the patients (80.0%), I 630 nm /I 590 nm of each individual patient's tumor sample was higher than that of normal sample.…”
Section: Discussionmentioning
confidence: 63%
“…It indicates that porphyrins accumulate more in tumor parts. The knowledge about the mechanisms of precursor 5-ALA lead to PpIX accumulation was demonstrated in many tumor diseases [48][49][50]. Our results showed that for the majority of the patients (80.0%), I 630 nm /I 590 nm of each individual patient's tumor sample was higher than that of normal sample.…”
Section: Discussionmentioning
confidence: 63%
“…As the steady-state fluorescence spectra for blood samples of cancer patients have been studied extensively, [8][9][10][11][12] the discussion will focus only on one pertinent observation. In the field of fluorescence spectroscopy, the relative intensities of different peaks are more important than the actual, absolute intensities.…”
Section: Discussionmentioning
confidence: 99%
“…We reported in our previous papers [8][9][10] on the results of steady-state measurements of blood components for cancer diagnosis using porphyrin as a biomarker. The results showed a significant discrimination accuracy to classify the diseased blood from normal blood.…”
Section: -6mentioning
confidence: 99%
“…The instrumentation and techniques employed in this study are similar to those previously described in the literature [8][9][10][11] . In order to highlight the major differences in spectral features of blood components in pregnant women, blood plasma and RBC samples were obtained from normal control and patients with thalassaemia.…”
mentioning
confidence: 99%
“…Further, haematoporphyrin is a mixture of many derivatives with protoporphyrin IX as the principal fluorescing component. The 585 nm band is attributed to the basic and 632 nm to the neutral form of haematoporphyrin [10][11][12] . The intensity of the band at 632 nm was twofold higher for the pregnant women, but only 50% for Thal patients when compared to the normal control group.…”
mentioning
confidence: 99%